La Calidad y su Enfoque Aplicado en la Educación, Caso Zongolica, Veracruz - Morales-Carrera, Uriel Alejandro; Contreras-Huerta, Sandra Patricia; Quiróz, Abril Camarillo; Vásquez, MarÃa Angelina Cervantes; González-Pérez, Manuel (European Scientific Journal, ESJ, 2019)
Quality is a concept that was born as a support to the economic system, with the help of different disciplines that have allowed to optimize the systems in general. The present investigation has the objective of explaining the concept of quality in education and evaluating one of the elements of the educational system that are teachers. The focus of the research is mixed, a questionnaire applied to students of a higher institution in Zongolica, Veracruz, Mexico. The instrument was validated with Cronbach’s Alpha and the contingency tables, tests of chi-square hypothesis and multiple correspondence analysis were applied. As a result, the main factors that evaluate the quality of the teacher’s class were identified. It is concluded that to understand the quality of education, a historical review of it is necessary for its correct application. La calidad es un concepto que nació como apoyo al sistema económico, con la ayuda de diferentes disciplinas que han permitido optimizar los sistemas en general. La presente investigación tiene el objetivo de explicar el concepto de calidad en la educación y evaluar uno de los elementos del sistema educativo que son los docentes. El enfoque de la investigación es mixto, un cuestionario aplicado a estudiantes de una institución superior en Zongolica, Veracruz, México. El instrumento se validó con el Alfa de Cronbach y se aplicaron las tablas de contingencia, las pruebas de hipótesis de chi-cuadrado y el análisis de correspondencia múltiple. Como resultado, se identificaron los principales factores que evalúan la calidad de la clase del profesor. Se concluye que para entender la calidad de la educación, es necesaria una revisión histórica de la misma para su correcta aplicación.